10.1152/physiolgenomics.00169.2022 (CrossRef Listing of Deleted DOIs, 2000)
For over a century, acetylcholine (ACh) was viewed primarily as a wired neurotransmitter of cholinergic nerves. However, accumulating evidence supports the view of the non-neuronal cholinergic system (NNCS) as an evolutionarily ancient autocrine and paracrine network operating across peripheral tissues. Rather than an extension of neuronal signaling, non-neuronal ACh can be viewed as a tissue-embedded chemical communication system positioned at the interface of cellular homeostasis and systemic neural reflexes. This review frames the NNCS as a network of tissue-resident ACh-producing cells that operates through mechanisms distinct from autonomic neural circuits. Across cardiovascular, immune, epithelial, metabolic, reproductive, and renal systems, NNCS signaling couples local cues to adaptive cellular responses. In the endothelium, ACh translates shear stress into M3 receptor-driven Ca2+ oscillations, endothelial nitric oxide synthase activation, and flow-mediated dilation, with indirect readouts of vascular cholinergic-nitric oxide coupling. In inflammatory and metabolic niches, macrophage-derived ACh regulates adipose tissue inflammation, supports peritoneal macrophage efferocytosis, and engages α7 nicotinic receptor pathways implicated in organ protection. At mucosal surfaces, brush/tuft cell signaling contributes to chemosensation, mucociliary clearance, luminal ACh release, anti-helminth immunity, and gut-brain communication. Non-neuronal ACh also modulates gametogenesis, placental transport, embryonic development, stem cell fitness, and conserved developmental mechanisms in honeybees. The kidney provides an informative example of layered regulation, where podocyte-derived ACh and tubular cholinergic receptor signaling are distinguished from vagus-spleen renal protective pathways and pelvic parasympathetic afferents regulating blood pressure. Finally, we address outstanding questions regarding ACh release, extracellular stability, spatial range, biomarkers, and tissue-selective therapeutic targeting.